Nicaragua : Sixth Review Under the Extended Credit Facility and Financing Assurances Review -Staff Report; Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Nicaragua's economic performance in 2010 was satisfactory. Real GDP grew, supported by strong consumption and investment. Bank credit started recovering while the financial system remained liquid and profitable. Exchange-rate and monetary policy have contributed to macroeconomic stability. The authorities plan to improve public financial management and also to adopt a legal framework and remain committed to contain the macroeconomic risks from external aid flows. They also welcomed the sixth review and Financing Assurances under the Extended Credit Facility (ECF) arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet